Induction of root-resistance by leaf-herbivory follows a vertical gradient - Erb, Matthias; Robert, Christelle Aurélie Maud; Turlings, Ted (My University, 2011)
Leaf-herbivory can lead to systemic changes in root metabolism and resistance. As yet, it is unknown if these changes affect the whole root system, or if they are more pronounced in the upper root parts, which are closer to the actual site of attack. As this spatial aspect may be an important determinant of the interactions that can be expected to occur within the rhizosphere, we investigated if leaf-herbivore induced root resistance differs between upper and lower roots of maize. We also tested if the density of leaf-herbivores correlates with intensity of the root response. The systemic increase in resistance was found to be more pronounced in the upper than the lower roots and was independent of leaf herbivore density. The results suggest that there is a vertical gradient in the strength of the root response following leaf-herbivory, and that soil organisms living closer to the surface may be more affected by leaf-attack than the ones living in deeper soil layers.
Keywords: Zea mays; Spodoptera littoralis; Diabrotica virgifera; induced; resistance; above- below-ground interactions; root defense; systemic; induced resistance; below-ground herbivory; plant defense; insect; coleoptera; phenology; maize; depth; soil